Review: Metode Sterilisasi Kimia dengan Etilen Oksida, Klorin Dioksida, dan Hidrogen Peroksida untuk Perlengkapan Medis - Putu Tarita Narisuari Karna, Ni; Amanda Hartono, Talitha; Putu Fiona Cista Dewi, Ni; Luh Desy Arianti, Ni (Journal of Comprehensive Science, 2025)
This review article aims to review and confirm the effectiveness of the chemicals ethylene oxide, chlorine dioxide, and hydrogen peroxide as sterilization agents with various parameters including temperature, humidity, pressure, and the ability to inhibit bacteria. The data analysis technique is literature study accessed through various online journal websites. The results of the review show that chemical sterilization methods with ethylene oxide, chlorine dioxide, and hydrogen peroxide have the potential to be used as significant sterilization agents in medical equipment. Each has advantages and disadvantages regarding its effectiveness for sterilization. The three chemical sterilization methods require comparative study research as a follow-up to assessing the effectiveness of chemicals using parameters, factors, variations in environmental conditions, as well as broader method development.